Structural characteristics and problems of beekeeping enterprises in aegean region example - Mustafa Bahadır Çevrimli; Engin Sakarya (Eurasian Journal of Veterinary Sciences)
Aim: In this study, structural characteristics and production problems of the beekeeping enterprises are examined in the Denizli, Mugla and Aydin provinces. Materials and Methods: The material of the research was provided through questionnaires from Turkish Association of Beekeepocooperatives member beekeeping enterprises. In the study, 73 enterprises were determined by stratified random sampling method. Frequency, and percent distribution of these enterprises according to their survey findings for the 2014- 2015 operating period. Differences between the two dependent groups were examined by the "Wilcoxon test". Results: The average age and beekeeping experience (year) of producers with primary school graduates (61.6%) was 50,08 ± 9,25 and 17,52 ± 11,02 respectively. In the enterprises where the rate of specialization is low (20.5%), average honey yield per hive was found to be 14.44 ± 6.56. Among the problems experienced in the production, not to be taken into village land (26,9%) and transportation (17,7%) took the first two places. The producers expect more support from the TAB Associations, where they are members, for storage-marketing and accommodation- transporting. Conclusion: According to the research findings, it can be said that the producer profile is important for sustainable beekeeping In particular, young producers are encouraged to use promoting policies in this area. Moreover, in terms of quality and productive honey production, bee diseases should be more effectively fighted and necessary limitations should be given to hive mobility. Current support policies should be revised.